Impairment of the еmotion control and social functioning in psychoses with depressive-paranoid symptoms - Zubatiuk, Oksana; Pyliagina, Galyna (Psychosomatic Medicine and General Practice, 2018)
Background. The problem of social functioning is one of the most relevant at the present stage. Over the past decades, first being in the sphere of interests of social psychiatry it has become one of the main focuses of research in clinical psychiatry. The number of works on this topic is increasing and motivating researchers to look for predictors of violations in social functioning. Recently, a lot of attention in these studies is devoted to the study of social cognition. Though, the studies are carried out within the framework of individual nosology types. At the same time, in our opinion, it would be interesting to expand the study using the syndromological approach in the "broad field" of psychotic disorders. Aim. Study of social cognition in patients with depressive-paranoid symptoms in psychotic disorders with the following nosology types: paranoid schizophrenia (F 20.0), schizoaffective disorder, depressive type (F25.1) and recurrent depressive disorder, current episode severe with psychotic symptoms of inpatient treatment at the stage of remission. Materials and methods. 61 patients have been examined. They are divided into three groups according to nosology types: 1 group - 21 patients with a diagnosis of paranoid schizophrenia (F 20.0 - Sch), group 2 - 23 patients diagnosed with depressive type of schizoaffective disorder (F 25.1 - SchAD) ) and group 3 - 17 patients suffering from recurrent depressive disorder (F 33.3 - RDD). The evaluation of social cognition, namely the level of emotion management, was conducted using the Russian-language version of the test of J. Meier, P. Selovey and D. Caruso "Emotional Intelligence" (MSCEIT V. 2.0) in the adapted version of E.A. Sergienko, I.I. Vetrova [1] *. One of the four branches of the test was used, namely, "Emotion Management", as well as PANSS and PSP scales. Results. The MSCEIT test emotion control scales are within the normal range, but the ratios are different in three groups: in the group of patients with Sch (and is the highest among the three groups), the indicators of the regulation scale of their own emotional states in relation to the indicators of emotional regulation of the states of other people prevail. The opposite picture is observed in the group of patients with SchAD. At the same time, the group of patients with RDD has low rates on both scales, but they are close to the lower boundary of the norm. Consequently, at each of the nosology types there is a specificity of cognitive impairment caused by the major disease. It is also indicative that the clinical picture of schizophrenia and schizoaffective disorder is similar but opposite in terms of MSCEIT indicators. The revealed link of indicators of the function of managing emotions and the level of social functioning allows us to determine the "targets" for rehabilitation programs in Sch (regulation of emotional states of other people) and RDD (regulation of their own emotional states). However, in this study, no such "targets" have been detected in the SchAD. There has been detected no clear link between the level of social functioning and the severity of the negative (deficient) symptoms, which for a long time has been considered the main factor of social maladaptation, but our data require additional research and more observations. Conclusion. The connection of certain psychopathological symptoms with the indicators of emotional management function allows to determine the "risk groups" among patients with each of the nosology types, which in advance can direct psychotherapeutic or psycho-rehabilitation measures focused on the correction of detected cognitive impairments.